Our mutual friend - Dickens, Charles, 1812-1870.; Sanders, Andrew, 1946- (New York : Knopf, 1994)
John Harmon, supposedly murdered on his way to London to claim his inheritance, takes a job under an assumed name and spies on the people who are trying to secure his late father's fortune.
"First included in Everyman's Library, 1907.".
Includes bibliography (p. xxvi-xxvii).
Adult
Keywords: Deception -- Fiction; Inheritance and succession -- Fiction; Poor families -- Fiction; Social classes -- Fiction; Deception -- Fiction; Inheritance and succession -- Fiction; Love stories; Poor families -- Fiction; Satire; Social classes -- Fiction; London (England) -- Fiction; London (England) -- Fiction; Love stories; Satire